The Structure of the Urartian Bureaucracy and a New Suggestion for Royal City Rulers - Armağan Tan (Tarih Dergisi)
With the Urartu Kingdom, a new settled culture, which was not seen before, emerged in these geographies. The places where this new culture and state structure were most clearly characterised were the royal cities. These cities, which have been identified through archaeological excavations, reflect the mountainous geographical characteristics of a new state authority north of the Taurus Mountains. In addition to the visible reflections of the Urartian material culture, the evaluation of the records on the administrative and bureaucratic structure as a whole provides important clues about the administrative positions and officials in the cities. The fact that Urartian written records are generally uniform texts of royal propaganda has made it possible to make some determinations only in the details of a few bureaucratic sources. Some “standards” that can be identified in the details of such sources, have enabled new conclusions to be recognised. In this context, especially the governors ( LÚEN.NAM), who are known to be the administrators of Urartian provinces, and the title LÚNAM, which we propose as the highest administrators of the royal cities, bring out the dissimilarity of provinces and royal cities not only for material culture but also according to administrative structure.